2010
DOI: 10.1016/j.yebeh.2010.01.010
|View full text |Cite
|
Sign up to set email alerts
|

The effect of temperament and neuropsychological functioning on behavior problems in children with new-onset seizures

Abstract: The present study is part of a larger project that seeks to identify factors that predict children’s behavioral, social, and cognitive adaptation to epilepsy. Children with seizures are more likely to have internalizing and externalizing behavior problems than either healthy children or children with other chronic illnesses. The present research examines risk factors for behavior problems. Early temperament and neuropsychological functioning, specifically executive function and language abilities, are evaluate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
44
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(52 citation statements)
references
References 44 publications
6
44
2
Order By: Relevance
“…Consistent with the conceptual framework of hot and cold EF skills, pediatric epilepsy studies show that EF and emotional/behavioral difficulties co-occur in youth with epilepsy 36,37 and are strongly related. 8,9 Moreover, improvements in behavior regulation among participants in the current trial suggest that Epilepsy Journey may contribute to improvements in both hot and cold EFs. Epilepsy Journey was designed to target both hot and cold EF, and problems identified for problem-solving cut across both cognitive and behavioral areas.…”
Section: Discussionmentioning
confidence: 78%
“…Consistent with the conceptual framework of hot and cold EF skills, pediatric epilepsy studies show that EF and emotional/behavioral difficulties co-occur in youth with epilepsy 36,37 and are strongly related. 8,9 Moreover, improvements in behavior regulation among participants in the current trial suggest that Epilepsy Journey may contribute to improvements in both hot and cold EFs. Epilepsy Journey was designed to target both hot and cold EF, and problems identified for problem-solving cut across both cognitive and behavioral areas.…”
Section: Discussionmentioning
confidence: 78%
“…Together this suggests that a high level of psychiatric problems in the boys group contributes to a high level of everyday behavioral executive dysfunction. Other studies have also suggested an association with behavioral/psychiatric problems and everyday executive problems in children with epilepsy (Baum et al, 2010;Ekinici, Titus, Rodopman, Berkem, & Trevathan, 2009).…”
Section: Discussionmentioning
confidence: 93%
“…Although deficits are greater in moderate to severe TBI (Schwartz et al, 2003; Catroppa et al, 2008; Yeates et al, 2002), existing research suggests that, relative to uncomplicated mild TBI and typically developing controls, children with complicated mild TBI often evidence impaired episodic memory and cognitive processing along with a diminished ability to manage cognitive interference (Levin et al, 2008). Neurocognitive deficits have been associated with persistent behavior problems and may be related to an impaired ability to regulate attention and emotional reactions (Barkley, 1997; Baum et al, 2010; Catroppa et al, 2008; Morgan & Lilenfeld, 2000 Schwartz et al, 2003). While some investigators have reported that verbal intelligence is negatively affected by neurological insult, such as TBI (Ewing-Cobbs et al, 1997; Verger et al, 2001), others have reported that verbal intelligence can be relatively unaffected when injury occurs later in development (Schmand, Smit, Geerlings, & Lindeboom, 1997; Anderson, Catroppa, Morse, Haritou, & Rosenfeld, 2000), suggesting that measures of verbal intelligence may provide reliable estimates of pre-morbid neurocognitive functioning after injury in adolescence (Lezak, Howieson, & Loring, 2004).…”
Section: Introductionmentioning
confidence: 99%